Identification of coral reef cover and invertebrate diversity in Pahawang Island Lampung Indonesia - Ismi Rakhmawati; Dina Maulina; Dewi Lengkana (Biological Environment and Pollution, 2022)
Pahawang Island is one of Lampung's tourist attractions known for its high organism biodiversity. The diversity of coral reefs contained in it causes Pahawang to have economic value for the audience. This study aims to determine the coverage and condition of coral reefs in the Pahawang area as a tourist attraction and identify the diversity of organisms within. This study used the Line Intercept Transect (LIT) method by dividing the plot of the observation area by six (6) identification points for data collection. Measurement data on each line transect, furthermore the closing value is calculated. The number of species was calculated by determining the value of the invertebrate diversity index. The results showed that the length of coral cover on Pahawang Island was 80.3% which lies in the “very good” category. Most of the corals have experienced bleaching which suggests that the corals are not in healthy condition. Species diversity shows that eleven (11) species reside in the Pahawang Island coral reef. The Shanon-Wiener diversity index value (H') 1.87 is categorized at the medium level. Therefore, the condition of coral cover on Pahawang Besar Island is still in the very good category.